(untitled) (Journal of Innovative Solutions for Eco-Environmental Sustainability, 2025)
The field experiment was conducted at Crop Research Centre of Sardar Vallabhbhai Patel University of Agriculture & Technology, Meerut (U.P.) during kharif season 2022 and 2023. The experiment was conducted under RBD design with ten nutrient management treatments viz. T1: Control, T2: Recommended dose of fertilizers NPK (120:60:40), T3: 50 % N through Dhaicha + 25% N through FYM + 25% N through Vermicompost, T4: 50 % N through Dhaicha + 25% N through FYM + 25% N through Vermicompost + Consortia + Biostimulant, T5: 25 % N through Dhaicha + 25% N through FYM + 50 % N through Vermicompost, T6: 25 % N through Dhaicha + 25% N through FYM + 50 % N through Vermicompost + Consortia + Biostimulant, T7: 1/3 N through Dhaicha + 1/3 N through FYM + 1/3 N through Vermicompost, T8: 1/3 N through Dhaicha + 1/3 N through FYM + 1/3 N through Vermicompost + Consortia + Biostimulant, T9: 50 % N through FYM + 50 % N through Vermicompost, and T10: 50 % N through FYM + 50 % N through Vermicompost + Consortia + Biostimulant. On the basis of pooled data, the yield attributes characters like: plant height, dry matter accumulation, number of effective tillers was found under treatment T2 (Chemical fertilizer 120:60:40). Similarly, yield attributing characters such as panicle length (27.61 cm), filled grain per panicle (72.57), 1000 grain weight (27.38 g) were recorded maximum under (Recommended dose of fertilizers, NPK :120:60:40) and found at par with 50 % N through Dhaicha + 25% N through FYM + 25% N through Vermicompost + Consortia + Biostimulant (T4). Highest grain yield (39.44 q/ha) and straw yield (64.47 q/ha)) was recorded under RDF followed by treatment T4, and T3 during both the years of experimentation.